METHODS OF DEVELOPING INNOVATIVE PEDAGOGY IN ENTREPRENEURSHIP - Elmuradova Lola Tojialievna (Journals Park Publishing, 2022)
Entrepreneurship is a creative activity aimed at searching for new areas of capital investment, creating new products, productions and improving existing ones, developing one's own advantages, effectively using various opportunities for profit. This article discusses about methods of developing innovative pedagogy in entrepreneurship.
Keywords: entrepreneurship, innovation, methods, opportunity, consumers, customers